Civil Society di Indonesia: Suatu Tantangan - Usman, Sunyoto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2002)
The idea of civil society has become an important discourse in the recent Indonesian political arena. This article discusses the possibility and challenge of developing civil society in Indonesia. Despite acknowlege the existence of the element of civil society in Indonesia, this article argues that there are obstacle to overcome in order to materialize civil society in Indonesia.